STEM facilitators training programme: trainee teachers’ perceptions of the impact on their personal growth as future teachers / Muhamad Furkan Mat Salleh, Nurul Akmal Md Nasir and Mohamad Hisyam Ismail - Mat Salleh, Muhamad Furkan; Md Nasir, Nurul Akmal; Ismail, Mohamad Hisyam (Universiti Teknologi MARA, 2020)
This study was conducted to find out the perceptions of Science and Mathematics trainee teachers on STEM Facilitator Training Program (SFTP) and to examine the impacts of SFTP on their personal growth as future teachers. The study employed a mixed-method design in which the data of the study were gathered through a short survey and group interview. The number of samples used for each method was dissimilar. 125 samples were selected by using stratified random sampling to answer the survey. The reliability of instruments used was determined by Cronbach’s alpha coefficient = 0.944 > 0.6. indicating that the items used are highly reliable. Additionally, the researchers selected 6 preservice teachers (3 respondents represented Science and Mathematics programmes respectively) to be involved in a semi-structured group interview. The study noted that they had high positive perception towards the programme. The design training programmes were suitable for the pre-service teachers as there is no significant difference in the respondents’ perceptions. Irrespective of the semesters, the results specify that there is no difference in terms of their perception after participating in the programme. The pre-service teachers joined the program as most of them saw SFTP as a good platform to expand their ability as future teachers and to have a real experience dealing with school students. The study also reported that there were several skills and knowledge that the respondents gained throughout their involvement in SFTP. It is clear that SFTP has impacted the personal growth of the respondents as future teachers as they claimed to be more confident in delivering Science and Mathematics content, were able to speak with more control and order, found that their instruction had improved and knew the important aspects needed to give an effective delivery in class. Overall, they believed SFTP had helped them improve their skills as future Science and Mathematics teachers.